Does the Use of Intraoperative Angiography Reduce the Incidence of Postoperative Wound and Flap Complications in Complex Lower Extremity Oncologic Reconstruction?. Issue 1 (July 2021) - Kapadia, Kailash; Dalena, Maragaret; Cavanaugh, Zachary; Ayyala, Haripriya; Ippolito, Joesph; Beebe, Kathleen; Benevenia, Joseph; Lee, Edward S.
Abstract : Introduction: Intraoperative laser angiography via indocyanine green (ICG) has become a valuable tool in objectively assessing tissue perfusion in reconstructive procedures. Studies have demonstrated the utility of ICG angiography (ICGA) for decreasing both mastectomy skin flap necrosis and wound healing complications in abdominal wall reconstruction. This tool has not been studied in lower extremity oncologic reconstruction. The objective of this study was to compare postoperative complications in lower extremity oncologic reconstruction managed with or without laser-assisted ICGA. Methods: A retrospective chart review was performed of patients undergoing complex lower extremity oncologic reconstruction at a single institution between 2000 and 2018. Patient information regarding demographics, comorbidities, operative procedures, and postoperative complications was analyzed. Results: Sixty-one patients were identified in our study. As some patients underwent multiple reconstructive surgeries, a total of 76 reconstructive procedures were analyzed. Patients with plastic surgery reconstruction using ICGA (n = 36) were compared with those without, non-ICGA (n = 40). No significant differences in age, sex, smoking status, chemotherapy, or radiation history were identified between cohorts. The total number of postoperative complications did not statistically differ between cohorts. There was no statistically significant difference in the number of required reoperation because of a postoperative complication between the ICGA and non-ICGA groups (0.44 vs 0.4). Conclusions: The incidence of postoperative wound complications after complex lower extremity oncologic reconstruction remains high. The findings of our study suggest that clinical judgment of flap and soft tissue viability, as compared with ICGA, may lead to comparable operative outcomes and be more cost-effective. Long-term follow-up and prospective studies are needed to further investigate this trend.